A new look at Sco OB1 association with Gaia DR2. Issue 1 (1st May 2020) - Yalyalieva, L; Carraro, G; Vazquez, R; Rizzo, L; Glushkova, E; Costa, E
ABSTRACT: We present and discuss photometric optical data in the area of the OB association Sco OB1 covering about 1 deg 2 . UBVI photometry is employed in tandem with Gaia DR2 data to investigate the three-dimensional structure and the star formation history of the region. By combining parallaxes and proper motions, we identify seven physical groups located between the young open cluster NGC 6231 and the bright nebula IC 4628. The most prominent group coincides with the sparse open cluster Trumpler 24. We confirm the presence of the intermediate-age star cluster VdB-Hagen 202, which is unexpected in this environment, and provide for the first time estimates of its fundamental parameters. After assessing individual groups membership, we derive mean proper motion components, distances, and ages. The seven groups belong to two different families. To the younger family (family I) belong several pre-main-sequence (PMS) stars as well. These are evenly spread across the field, and also in front of VdB-Hagen 202. VdB-Hagen 202, and two smaller, slightly detached, groups of similar properties form family II, which do not belong to the association, but are caught in the act of passing through it. As for the younger population, this forms an arc-like structure from the bright nebula IC 4628 down to NGC 6231, as previously found. Moreover, the PMS stars density seems to increase from NGC 6231 northward to Trumpler 24.